Expectations of modernity : myths and meanings of urban life on the Zambian Copperbelt. - Ferguson, James (Perspectives on Southern Africa ;, 1999)
Once lauded as the wave of the African future, Zambia's economic boom in the 1960s and early 1970s was fueled by the export of copper and other primary materials. Since the mid-1970s, however, the urban economy has rapidly deteriorated, leaving workers scrambling to get by. Expectations of Modernity explores the social and cultural responses to this prolonged period of sharp economic decline. Focusing on the experiences of mineworkers in the Copperbelt region, James Ferguson traces the failure of standard narratives of urbanization and social change to make sense of the Copperbelt's recent history. He instead develops alternative analytic tools appropriate for an "ethnography of decline."